Toward a cognitive classical linguistics the embodied basis of constructions in Greek and Latin - Mocciaro, Egle ca. 20./21. Jhr.; Short, William Michael 1977- (Warsaw Berlin De Gruyter Open Poland, 2019)
This volume gathers a series of papers that bring the study of grammatical and syntactic constructions in Greek and Latin under the perspective of theories of embodied meaning developed in cognitive linguistics. Building on the momentum currently enjoyed by cognitive-functional approaches to language within the field of Classics, its contributors adopt, in particular, a 'constructional' approach that treats morphosyntactic constructions as meaningful in and of themselves. Thus, they are able to address the role of human cognitive embodiment in determining the meanings of linguistic phenomena as diverse as verbal affixes, discourse particles, prepositional phrases, lexical items, and tense semantics in both Greek and Latin
Frontmatter --Contents --Introduction. Toward a cognitive classical linguistics /Mocciaro, Egle / Short, William Michael --1 Aspect and construal A cognitive linguistic approach to iterativity, habituality and genericity in Greek /Allan, Rutger J. --2 A construction-grammar analysis of ancient Greek particles /Drummen, Annemieke --3 The embodied basis of discourse and pragmatic markers in Greek and Latin /Fedriani, Chiara --4 Reversive constructions in Latin: the case of re- (and dis- ) /Brucale, Luisa --5 Autόs and the center-periphery image schema /Bonifazi, Anna --6 Aspects of aural perception in Homeric Greek /Luraghi, Silvia / Sausa, Eleonora --7 The role of spatial prepositions in the Greek lexicon of garments /Papadopoulou, Maria --8 Metaphor by any other name. A cognitive linguistic reassessment of Aristotle's theory of metaphor /Membrez, Greg --9 Animus inscriptus An out-of-body embodiment/Collins, Christopher --10 Metaphorical word order /D'Anselmi, Luca --Index
In English
Keywords: Greek Language -- Grammar; Latin language -- Grammar; Cognitive grammar; LANGUAGE ARTS & DISCIPLINES ; Linguistics ; Historical & Comparative; Latin language ; Grammar; Greek language ; Grammar; History, Ancient; Aufsatzsammlung